“Awakened Muse” by Ihor Kalynets in the interartistic dialogue with Oleksa Novakivskyi - Savchuk, Hryhorii (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The purpose of the article is to provide an alternative reading of the title of Ihor Kalynets’s collection “Awakened Muse” based on an intermedial analysis of poems written under the influence of Olexander Novakivskyi’s paintings. Ihor Kalynets felt the nerve of rebellion and the all-consuming element of music in the livestory and creative work of the artist from Lviv and conveyed them through the poem “Muse”. The poem presents a collective image of Anna-Maria, the wife, who inspired O. Novakivskyi’s artistic work, and who really was his muse. The created visual image continues the theme of “Stabat Mater” (“Grieving Mother”) in the worldwide art. The fact is that the rebellious, expressive nature of the artist’s work required its opposite for balance, which was embodied in the figure of his wife and muse Anna-Maria. In I. Kalynets’s interpretation, Anna-Maria “had” to be a muse for her husband, that is, the wife “had” to devote herself to the service of art, realizing that she would have to experience certain sacrifices for this.The integrity of O. Novakivskyi’s painting “‘Self-Portrait’ with the wife” is ensured by the principle of projection: the figure of the man in the composition of the canvas is projected onto the figure of the woman, who in the background seems to echo her husband with her posture, the position of her left hand, which supports the head. The artist looks at the recipients of the painting, from the bottom up and to the right, while Anna-Maria looks from the top down. Using the resources of geometric terminology, these gazes could be called “fleeting” because they lie in different planes and do not intersect. I. Kalynets interprets the expressions of the characters’ faces in different ways: the artist’s face is “wise and sharp” while Anna Maria’s face is “hopeless and beautiful”. This juxtaposition cannot be called symmetrical, it means that the semantics of the images do not enter into polar relationship. This juxtaposition is rather asymmetrical and “transient”, just like the gazes in the painting are.I. Kalynets chose the painting “Awakening” as an object for the ekphrasis and interpretive narrative, perhaps because O. Novakivskyi, with his fresh modernist’s perspective, was the first to innovatively depict Ukraine as a child, almost a teenager. The element of sunlight in the painting and I. Kalynets’s surprisingly harmonious ekphrasis affirm positivity, hope and faith into the future, in which there will be no space for suffering, and suggest that the child, as well as Ukraine, has their whole life ahead of them.Based on the intermedial analysis, the following conclusions were drawn: 1. Under the right conditions, the muse awakens to inspire the artist. These conditions are related to historical progress, but above all, to the peculiarities of individual evolution of the author. 2. The artist and the muse are in the relationship of dialectical unity, which drives them both in their development. 3. The images of the muse and awakening lead directly to the image of Ukraine, which is awakening on the way to its independence. The divine powers play the leading role in this process.